The Relationship of Pregnant Mother's Compliance with Antenatal Care with the Event of Preeclampsia in Tanjung Bingkung Puskesmas - Rhandyka Rafli; Indah Salsabila; Ferry Iskandar; Debie Anggraini; Dian Ayu Hamama Pitra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Preeclampsia is an increase in blood pressure experienced by pregnant women, at gestational age above 20 weeks which is treated with routine antenatal visits, this research was conducted at the Tanjung Bingkung Health Center because there is a behavior of young mothers who are ashamed to admit their pregnancy. The purpose of this study was to determine the relationship between pregnant women's adherence to antenatal care with the incidence of preeclampsia at the Tanjung Bingkung Health Center. This research method includes obstetrics and gynecology, conducted at the Tanjung Bingkung Health Center from September to November 2020. The research design was correlation analytic and case control design. The research target population was 54 samples selected by simple random sampling. Data analysis using SPSS application. So the results of this study explain that the compliance of pregnant women in antenatal care is 67% seen from the age of the highest adherence at the age of 20-35 years (80%) and seen from the parity status the highest is multigravida (68%). The incidence of preeclampsia is 13%, judging by age, the highest incidence occurs at the age of 20-35 years (80%) and from multigravida pregnant women (70%). The relationship between adherence of pregnant women to antenatal care with the incidence of preeclampsia, found p value > 0.05 with the conclusion that there is no relationship between adherence of pregnant women to antenatal care with the incidence of preeclampsia.